2016
DOI: 10.1177/0017896916644001
|View full text |Cite
|
Sign up to set email alerts
|

What motives are important for participation in leisure-time activities at Swedish youth centres?

Abstract: Objective: This study aimed to explore the motives of young people in multicultural suburbs for participating in youth-centre activities. Design and setting: The study employed practice-based research with a focus on collaboration and methodological diversity. Data on motives for participation were collected in spring 2013 at two non-governmental organisation (NGO)-run youth centres located in the suburbs of two cities in Sweden using surveys and focus-group interviews. Method: The study used mixed methods, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The proportion of young people who self-report the different motives as ‘very important’ ( n =163). From Geidne et al [20]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportion of young people who self-report the different motives as ‘very important’ ( n =163). From Geidne et al [20]. …”
Section: Resultsmentioning
confidence: 99%
“…Data were collected through annual surveys on three occasions: the first emphasising who participates [19], the second the motives of participation [20] and the last what the young people gained from participation. Both individual and group interviews were made, deepening the questions above, as well as focusing on the strategies used in every-day activities [17].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the rationale for involvement and its stance as a protective factor against crime and violence is unclear. A research done on Swedish adolescents found that seeing friends, doing something fun or interesting were the main motivations for social activity participation [ 39 ]. However, this type of qualitative inquiry is missing in the South African context where motivations may differ based on socio-cultural and crime differences in the two countries.…”
Section: Discussionmentioning
confidence: 99%